Gradient optimization of optimal choice the multiplicity of control-retrofit procedures for technological processes under the restricted resource taking into account various types of defects - Rotshtein, O. P.; Shtovba, S. D.; Kozachko, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
In work the gradient algorithm of optimal choice the multiplicity of control-retrofit procedures in technological process is offered in case, when the diverse of defects types are taking into account. The offered algorithm functions well, when admissible probability threshold for diverse types of defect is approximately equal. For tasks, in which these probabilities for diverse defects types differ greatly, the offered algorithm sometimes fails.